Deferasirox in the management of iron overload in patients with myelofibrosis treated with ruxolitinib: The multicentre retrospective RUX‐IOL study. (8th February 2022) - Elli, Elena Maria; Di Veroli, Ambra; Bartoletti, Daniela; Iurlo, Alessandra; Carmosino, Ida; Benevolo, Giulia; Abruzzese, Elisabetta; Bonifacio, Massimiliano; Bergamaschi, Micaela; Polverelli, Nicola; Caramella, Marianna; Cilloni, Daniela; et al.
Summary: Deferasirox (DFX) is used for the management of iron overload (IOL) in many haematological malignancies including myelofibrosis (MF). The 'RUX‐IOL' study retrospectively collected 69 MF patients treated with ruxolitinib (RUX) and DFX for IOL to assess: safety, efficacy in term of iron chelation response (ICR) and erythroid response (ER), and impact on overall survival of the combination therapy. The RUX–DFX therapy was administered for a median time of 12.4 months (interquartile range 3.1–71.2). During treatment, 36 (52.2%) and 34 (49.3%) patients required RUX and DFX dose reductions, while eight (11.6%) and nine (13.1%) patients discontinued due to RUX‐ or DFX‐related adverse events; no unexpected toxicity was reported. ICR and ER were achieved by 33 (47.8%) and 32 patients (46.4%) respectively. Thirteen (18.9%) patients became transfusion‐independent. Median time to ICR and ER was 6.2 and 2 months respectively. Patients achieving an ER were more likely to obtain an ICR also ( p = 0.04). In multivariable analysis, the absence of leukocytosis at baseline ( p = 0.02) and achievement of an ICR at any time ( p = 0.02) predicted improved survival. In many MF patients, the RUX–DFX combination provided ICR and ER responses that correlated with improved outcome in the absence of unexpected toxicities. This strategy deserves further clinical investigation.